The Emerald handbook of quantum storytelling consulting - Boje, David M.; Sanchez, Mabel (Emerald Publishing Limited, 2018)
There is a paradigm shift happening in storytelling consulting. The oldone-story-fits-all consulting paradigm - helping companies to brand their founding story, do elevator pitches, and deliver stump speeches - is giving way to quantum storytelling consulting. The quantum age has moved away from a mechanist, Newtonian, simple-cause-and-effect understanding of reality and life, and storytelling consulting is now about an ensemble of stories rather than a single pitch. It's about developing the spaces for storytelling processes; it's about the times when storytelling is emerging; and it's about the kinds of 'mattering' or material agency that the storytelling has. In the quantum age, space, time, and mattering have no separation; instead, 'spacetime mattering' storytelling emerges, self-organizes, and creates change management. It is no longer thecase that one narrative fits all. Rather, it is the interplay of many living stories that create the complex forces of change within organizations. 'The EmeraldHandbook of Quantum Storytelling Consulting' collects the findings of quantum storytelling researchers and consultants to develop a practical understanding of quantum storytelling consulting by sharing case examples, describing how to enact specific practices, and outlining how to conduct research into the impact and consequences of quantum thinking.